2011
DOI: 10.1016/j.wear.2010.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 3D surface topography in 5-axis milling

Abstract: Within the context of 5-axis free-form machining, CAM software offers various ways of toolpath generation, depending on the geometry of the surface to be machined. Therefore, as the manufactured surface quality results from the choice of the machining strategy and machining parameters, the prediction of surface roughness in function of the machining conditions is an important issue in 5-axis machining. The objective of this paper is to propose a simulation model of material removal in 5-axis based on the N-buf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…If we consider the Z-buffer or N-buffer methods applied to a realistic description of both the tools and the machining path, earlier work have shown that it is possible to simulate the resulting geometry on small portions of the surface in a few minutes [8,9]. Simulation results are very close to experimental results but the simulated surfaces have an area of a few square millimeters with micrometer resolution (Fig.…”
Section: Introductionmentioning
confidence: 52%
“…If we consider the Z-buffer or N-buffer methods applied to a realistic description of both the tools and the machining path, earlier work have shown that it is possible to simulate the resulting geometry on small portions of the surface in a few minutes [8,9]. Simulation results are very close to experimental results but the simulated surfaces have an area of a few square millimeters with micrometer resolution (Fig.…”
Section: Introductionmentioning
confidence: 52%
“…For laser based processes, simulation of the metal flow phenomenon with regards to thermic evolution is complex, and the calculation times even for a small area make it hard to be used efficiently. For conventional processes such as milling process however, some studies propose a robust simulation of the final surface regarding operating parameters [12]. The choice of a method would depend on the physical principle of the manufacturing process.…”
Section: Problem Definitionmentioning
confidence: 99%
“…Another, more common, modeling of the surface topography is based on the buffer method to specify the height of the material remaining on a surface. This model is used for a bull nose end mill [14][15][16] or a ball end mill [17][18][19]. Denkena et al [20] complete this model with a stochastic surface topography contribution.…”
Section: Introductionmentioning
confidence: 99%